ANALISIS PELAKSANAAN DISTRIBUSI PENJUALAN PRODUK PERCETAKAN BUKU ( Kasus Kantor Perwakilan PT. Penerbit Erlanga di Pekanbaru ) - Dicky Febrian; Kasmiruddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Each company’s goods and services will not be apart from the problem ofdistribution of goods produced. The manufacturer reserves the right to determine distributionpolicy which will be selected and adjusted with the type of goods as well as the extent of asales force that will be used. If the firm is in the increasingly sharp competition, companiesmust immediately conduct a study of its market. Market research aims to identify the needsand tastes of consumers and, if possible, stimulating demand and creating new agents. Andestablishment is successful in marketing if the company can market the stuff widely andevenly with a maximum benefit.Therefore, the management company is required to always remain responsive inadapting to continuous environmental change occurs and has effects on the economic state ofthe company, because that company is required to determine the effective distributionchannels. This research was conducted in PT Penerbit Erlangga Representative Office,located at jalan Soekarno-Hatta Pekanbaru. Penerbit Erlangga is central in Jakarta.Thisstudy aims to determine distribution that performed by PT Penerbit Erlangga RepresentativeOffice to increase their sales volume.Authors conclude from the results of this study, the method used in this research isdescriptive method, where as the type of research using quantitative. From the result ofresearch, actually PT Penerbit Erlangga Representative just can perform fine to standard oftime distribution and geography than the other : Transportation, Service of distribution, andschedule of distributionKeywords : Distribution, Sales, Management, Marketing